The oral-gut-circulatory axis: from homeostasis to colon cancer - Tortora, Sofia C.; Agurto, Maria Gonzalez; Martello, Laura A. (Frontiers in Cellular and Infection Microbiology, 2023)
The human microbiota is widely recognized as providing crucial health benefits to its host, specifically by modulating immune homeostasis. Microbial imbalance, known as dysbiosis, is linked to several conditions in the body. The oral cavity and gut are the two largest microbial communities playing a major role in microbial-associated diseases. While the oral-gut axis has been previously explored, our review uniquely highlights the significance of incorporating the circulatory system into this axis. The interaction between immune cells, inflammatory factors, circulating bacteria, and microbial metabolites influences the homeostasis of both the oral and gut microbiota in a bidirectional manner. In this comprehensive review, we aim to describe the bacterial components of the oral-gut-circulatory axis in both health and disease, with a specific focus on colon cancer.